2021
DOI: 10.3390/antibiotics10050591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Prescribing Patterns of First-Line Antibiotics in English Primary Care: A Longitudinal Analysis of National Prescribing Dataset

Abstract: The COVID-19 pandemic has impacted on public access to health services. This study aimed to investigate the impact of COVID-19 pandemic on commonly prescribed first-line antibiotics in English primary care. A secondary analysis of publicly available government data pertaining to primary care prescribing was conducted. A list of twenty first-line antibiotics used to treat common infections was developed following the National Institute of Clinical Excellence (NICE) guidelines. All primary care prescription and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
(23 reference statements)
5
19
0
1
Order By: Relevance
“…A study in Iceland showed that there was an increase in the total number of medication prescriptions; however, the number of antibiotic prescriptions remained stable [ 36 ]. English data from primary care showed that the prescribing of antibiotics decreased significantly [ 37 , 38 ] and also, data specifically from OOH care showed a reduction in antibiotic prescribing during the first wave of COVID-19 [ 39 ]. However, when looking at the number of prescriptions per contact, during the first months of the pandemic, there is a significant increase, possibly explained by an increase in inappropriate antibiotic use in telephone consultations [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Iceland showed that there was an increase in the total number of medication prescriptions; however, the number of antibiotic prescriptions remained stable [ 36 ]. English data from primary care showed that the prescribing of antibiotics decreased significantly [ 37 , 38 ] and also, data specifically from OOH care showed a reduction in antibiotic prescribing during the first wave of COVID-19 [ 39 ]. However, when looking at the number of prescriptions per contact, during the first months of the pandemic, there is a significant increase, possibly explained by an increase in inappropriate antibiotic use in telephone consultations [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also imperative to consider healthcare professionals' and wider stakeholders' experiences of delivering cancer services. Roles of non-medical healthcare professionals including pharmacists can be diversified to support cancer services [43][44][45] including their roles in administering COVID-19 vaccination. 46 Novel, faster and accurate methods of detection of symptomatic and asymptomatic COVID-19 can minimise disruptions to the services in the future.…”
Section: Resilience and Coping Mechanismsmentioning
confidence: 99%
“…In contrast to the consumption data from hospitals, where antibiotic prescriptions initially increased despite relatively low detected rates of bacterial co-infections in COVID-19 patients [ 13 , 14 ], antibiotic use in primary care dropped. The magnitude of this reduction has ranged between 30 and 40% and has been notably greater for antibiotics primarily used for ARTIs [ [15] , [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%